2002
DOI: 10.1055/s-2002-25285
|View full text |Cite
|
Sign up to set email alerts
|

Magnifying Endoscopy, Stereoscopic Microscopy, and the Microvascular Architecture of Superficial Esophageal Carcinoma

Abstract: Observation of the microvascular architecture of superficial esophageal carcinoma is useful in the diagnosis of the depth of invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
218
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(225 citation statements)
references
References 9 publications
3
218
0
4
Order By: Relevance
“…[19][20][21][22] Inoue et al reported the terminal capillary inside the epithelial papillae of the normal squamous epithelium named intra-papillary capillary loop (IPCL).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22] Inoue et al reported the terminal capillary inside the epithelial papillae of the normal squamous epithelium named intra-papillary capillary loop (IPCL).…”
Section: Discussionmentioning
confidence: 99%
“…Japanese endoscopists currently apply these features for diagnosing the depth of tumor invasion, and in this context, high accuracy of preoperative magnifying endoscopy has been reported. [20][21][22] Considering these observations, we compared the four different categories of normal squamous epithelium, LGIN (borderline malignancy), M1 and M2 cancer, and M3 or deeper cancer.Using cancerous and precancerous lesion of the esophagus, Shamma et al 5 reported that the COX-2 immunoreactivity score was highest in high-grade dysplasia, and then gradually decreased according to cancer progression (at the present time, ''highgrade dysplasia'' is considered to be ''high-grade intraepithelial neoplasia'' in the Japanese classification, 1 which is included in ''M1 and M2 cancer'' in the present report). Our present study revealed positive staining for 71.9% of COX-2 and 80.7% of iNOS among M1, M2 regions.…”
mentioning
confidence: 99%
“…In the NBI mode, normal laryngeal mucosa consists of submucosal vessels (appearing green) connecting with an arborescent vascular network (appearing dark brown). Abnormalities of these intraepithelial papillary capillary loop (IPCL), located beneath the basement membrane of epithelium, are usually classified in accordance with their shape changes; such changes have been found to predict the depth of superficial cancer invasion (134,135). Classification of laryngeal lesions has been reported in Figure 4.…”
Section: Narrow Band Imaging (Nbi)mentioning
confidence: 99%
“…Kumagai et al examined surgically resected specimens of superficial esophageal cancer by stereoscopic microscopy, using the Microfil injection technique (2). Furthermore, they histomorphometrically measured the caliber of superficial blood vessels of esophageal tumors and found that vessel caliber gradually increased in parallel to the depth of invasion (16).…”
Section: Discussionmentioning
confidence: 99%